Dollars, Debt, and Deficits : Sixty Years After Bretton Woods. (International Monetary Fund, 2005)
This book examines the challenges facing the international monetary and financial system, as well as the future role of the Bretton Woods institutions in addressing those challenges. The volume is based on the proceedings of a 2004 conference cosponsored by the Banco de Espana and the International Monetary Fund to commemorate the 60th anniversary of the Bretton Woods meetings in July 1944. The chapters look at global imbalances, exchange rate issues, debt in emerging economies, and innovations in private and multilateral lending.